1987
DOI: 10.1099/00221287-133-7-1743
|View full text |Cite
|
Sign up to set email alerts
|

Progress of O-Acetylation and Cross-linking of Peptidoglycan in Neisseria gonorrhoeae Grown in the Presence of Penicillin

Abstract: The synthesis, cross-linking and O-acetylation of gonococcal peptidoglycan in growing cells were studied by following incorporation of radioactive glucosamine and separation of the SDS-insoluble peptidoglycan into uncross-linked (monomer) and cross-linked (dimer and oligomer) fragments. Cultures to which penicillin or piperacillin at concentrations near the minimum growth inhibitory concentration (MIC) had been added 20 min before the radioactive label were compared with controls. The beta-lactams affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Taken together, these observations support the previous conclusions that the 0 acetylation of PG is a maturation process (9,17,18,(21)(22)(23)33) and that N-linked acetate is transferred to the C-6 position of muramyl residues (12). For N-*O transacetylation to occur within the cell-free system, the autolysins documented to be present (3,8) would have to be catalytically active since, according to the current hypothesis (12), PG turnover is associated with the process of 0 acetylation.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Taken together, these observations support the previous conclusions that the 0 acetylation of PG is a maturation process (9,17,18,(21)(22)(23)33) and that N-linked acetate is transferred to the C-6 position of muramyl residues (12). For N-*O transacetylation to occur within the cell-free system, the autolysins documented to be present (3,8) would have to be catalytically active since, according to the current hypothesis (12), PG turnover is associated with the process of 0 acetylation.…”
supporting
confidence: 78%
“…It is known to be stimulated either when cells are in the stationary phase of growth or under conditions which mimic the stationary phase (e.g., under the influence of chloramphenicol [28] acetylation occurs within the PG sacculus and outside the cytoplasm (9,17,18,(21)(22)(23)33). Indeed, PG 0 acetylation has also been demonstrated to continue in an in vitro P. mirabilis PG biosynthetic system (25), albeit to a lesser extent than that observed in vivo.…”
mentioning
confidence: 99%
“…The observation that the DP of the chitooligosaccharides had to be Ն3 to serve as acceptor for PatB is consistent with early reports concerning the O-acetylation of PG in N. gonorrhoeae, Proteus mirabilis, and S. aureus. These earlier biochemical studies demonstrated that O-acetylation occurs shortly after transglycosylation and transpeptidation of Lipid II (undecaprenyl-bound GlcNAc-MurNAc-pentapeptide) (29,(35)(36)(37)(38)(39), thus involving PG chains and not the precursor disaccharide. The modest improvement in the K m and specificity constant for the chitooligosaccharides with increasing DP to 5/6 suggests that PatB, like many other carbohydrate-active enzymes, including lysozyme (40), probably has several sugar binding subsites in its active site.…”
Section: Discussionmentioning
confidence: 97%
“…Substantial evidence indicates that the O acetylation of peptidoglycan occurs after the cross-linking of peptide side chains by transpeptidation (4,12,17,18,(25)(26)(27)36), and more recently, an N3O-acetyltransferase has been proposed to catalyze the transfer of acetyl groups from the N-2 position of either glucosaminyl or muramyl residues to the C-6 position of the latter during the turnover of peptidoglycan (14,15). In the present study, we have investigated the relationship between the expression of the aac(2Ј)-Ia gene in P. stuartii and the O acetylation of its peptidoglycan.…”
mentioning
confidence: 99%